Applying an Ecological Systems Framework: How a Historically Black University, a Predominately White Institution, and a Public School System Created a Collaborative Undergraduate Research Experience. Issue 1 (23rd November 2022) - Watkins, Charity S; Cason, Xavier; Greenwald, Alec David; Dunston, Yolanda L; Vo, Quynh-Chi
Abstract: Guided by the National Association of Social Workers' Code of Ethics and measures of competence provided by the Council on Social Work Education, the social work field serves as a model for strategies that promote collaboration across difference, strengths-based advocacy with communities, and education through engagement. These values and perspectives are relevant beyond social work, as they are applied in various disciplines and settings including educational systems. In academic environments, social workers and educators work together to facilitate the development of knowledge, attitudes, skills, and interactions that are individualized, empowering, equitable, strengths-focused, and culturally responsive among all individuals serving children in the school setting, including volunteers from the surrounding community. Using an ecological systems framework to explore the bidirectional relationships between individual student experiences, peer interactions, university–community connections, and collaboration with a local public school district, this article identifies how an interinstitutional student-engaged research partnership between a historically Black university, a predominately White institution, and a local school district models the power of a diverse and equitable collaboration with each subsystem positively contributing to the realization of social work values and ethics. Implications for public school students, staff, and surrounding communities are discussed.